2015
DOI: 10.1109/tpds.2014.2346200
|View full text |Cite
|
Sign up to set email alerts
|

All-To-All Broadcast in Hexagonal Torus Networks On-Chip

Abstract: Hexagonal torus networks are special family of Eisenstein-Jacobi (EJ) Networks which have gained popularity as good candidates network On-Chip (NoC) for interconnecting Multiprocessor System-on-Chips (MPSoCs). They showed better topological properties compared to the 2D torus networks with the same number of nodes. All-to-all broadcast is a collective communication algorithm used frequently in some parallel applications. Recently, an off-chip all-to-all broadcast algorithm has been proposed for hexagonal torus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For instance, the problems related to image processing and computer vision [2,3,4,5,6,7,27] are solved based on the implementation of parallel algorithms. Furthermore, some studies on one-to-all and all-to-all broadcasting can be found in [15,21,26]. In one-to-all broadcasting, a source node sends its message to every other node in the network.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the problems related to image processing and computer vision [2,3,4,5,6,7,27] are solved based on the implementation of parallel algorithms. Furthermore, some studies on one-to-all and all-to-all broadcasting can be found in [15,21,26]. In one-to-all broadcasting, a source node sends its message to every other node in the network.…”
Section: Introductionmentioning
confidence: 99%